Emotional Substrates In Neuroticism: The Reactions To Arousal-evoking Stimuli Of Various Strengths - Nasir Yusof; Faruque Reza; Nik NurAzhani Anuar; Roslee Ahmad (Ibn Sina Trust, 2024)
Volume :19 No: 2